CARBON PRICING AS A REVENUE STREAM FOR GREENER FUTURE - Riyono, Kenley Maccauley; Stanley, Nicklaus; Widianingsih, Luky Patricia (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes. This study aims to determine whether carbon pricing can increase the capacity of renewable energy mediated by government revenue. Research Methods. The sample used is 22 countries that have implemented a carbon price either carbon tax or emissions trading system from 2019 to 2023. The analysis method uses panel data regression. Research Results and Findings. The results show that government revenue can fully mediate the impact of carbon pricing on renewable energy capacity. This result indicates that carbon pricing plays a vital role in social and economic as a domestic climate policy and is the most effective solution to increase the use of renewable energy. The implication of this research result can be used as a consideration for countries to design and implement carbon pricing to be more effective.